Prognostic relevance of preoperative bilirubin-adjusted serum carbohydrate antigen 19-9 in a multicenter subset analysis of 179 patients with distal cholangiocarcinoma. Issue 11 (November 2019) - Bolm, Louisa; Petrova, Ekaterina; Weitz, Jürgen; Rückert, Felix; Wittel, Uwe A.; Makowiec, Frank; Lapshyn, Hryhoriy; Bronsert, Peter; Rau, Bettina M.; Khatkov, Igor E.; Bausch, Dirk; Keck, Tobias; et al.
Abstract: Background: Distal cholangiocarcinoma (DCC) is a rare malignancy and validated prognostic markers remain scarce. We aimed to evaluate the role of serum CA19-9 as a potential biomarker in DCC. Methods: Patients operated for DCC at 6 high-volume surgical centers from 1994 to 2015 were identified from prospectively maintained databases. Patient baseline characteristics, surgical and histopathological parameters, as well as overall survival after resection were assessed for correlation with preoperative bilirubin-adjusted serum carbohydrate antigen 19-9 (CA19-9). Preoperative CA19-9 to bilirubin ratio (CA19-9/BR) was classified as elevated (≥ 25 U/ml/mg/dl) according to the upper serum normal values of CA19-9 (37 U/ml) and bilirubin (1.5 mg/dl) giving a cut-off at ≥ 25 U/ml/mg/dl. Results: In total 179 patients underwent resection for DCC during the study period. High preoperative CA19-9/BR was associated with advanced age and regional lymph node metastases. Median overall survival after resection was 27 months. Elevated preoperative serum CA19-9/bilirubin ratio (HR 1.6, p = 0.025), T3/4 stage (HR 1.8, p = 0.022), distant metastasis (HR 2.5, p = 0.007), tumor grade (HR 1.9, p = 0.001) and R status (HR 1.7, p = 0.023) were identified as independent negative prognostic factors following multivariable analysis. Conclusion: Elevated preoperative bilirubin-adjusted serum CA19-9 correlates with regional lymph node metastases and constitutes a negative independent prognostic factor after resection of DCC.